2019
DOI: 10.6007/ijarbss/v9-i6/5969
|View full text |Cite
|
Sign up to set email alerts
|

Seeking of Agriculture Information through Mobile Phone among Paddy Farmers in Selangor

Abstract: Introduction: Mobile phone is one of the communication tools that have always mattered in many fields included agriculture. The development of the agriculture sector in the rural area is significant to diminish poverty among farmers. Agricultural activities are known to provide opportunities for employment and generating income in the rural area. Poverty can be reduced through adequate investment and improvement in the agriculture sector. Enhancing the use of mobile phone will empower farmers with relevant agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The results presented in Figure 4 indicated that the majority of the respondents do not use mobile phones as a source of their agricultural information However, there are some types of agricultural information that farmers use mobile phones to obtain, such as information related to pest control and disease management which ranked first with 42.8%, followed by the information related to agricultural recommendations on varieties, planting dates, irrigation, plowing, etc., that came in the second rank as mentioned by 37.5% of respondents, while information related to marketing and weather came in the last ranks, which is consistent with the study results obtained by Ramli et al (2019) in Selangor Province, Malaysia on the rice farmers' search for agricultural information through the mobile phone In the forefront of this information, those related to pest control, while recommendations for weather and marketing information came in the last ranks. These findings also agreed with that mentioned by Alibu et al (2016) where information on pest control ranked first, while weather information came in a lagging position.…”
Section: Respondents' Use Of Mobile Phones For Agricultural Purposesupporting
confidence: 87%
“…The results presented in Figure 4 indicated that the majority of the respondents do not use mobile phones as a source of their agricultural information However, there are some types of agricultural information that farmers use mobile phones to obtain, such as information related to pest control and disease management which ranked first with 42.8%, followed by the information related to agricultural recommendations on varieties, planting dates, irrigation, plowing, etc., that came in the second rank as mentioned by 37.5% of respondents, while information related to marketing and weather came in the last ranks, which is consistent with the study results obtained by Ramli et al (2019) in Selangor Province, Malaysia on the rice farmers' search for agricultural information through the mobile phone In the forefront of this information, those related to pest control, while recommendations for weather and marketing information came in the last ranks. These findings also agreed with that mentioned by Alibu et al (2016) where information on pest control ranked first, while weather information came in a lagging position.…”
Section: Respondents' Use Of Mobile Phones For Agricultural Purposesupporting
confidence: 87%
“…the most standard communication function/toll is WhatsApp followed by Facebook, Messenger, WeChat, and Telegram (98.1%), (55.6%), (36.8%) and (25.0%) respectively. The findings indicate that the WhatsApp app can support our society to broadly distribute and share information regarding agriculture and rural development (MCMC 2018 andRamli et al, 2019).…”
Section: Role Of Mobile Phones In Agriculture Developmentmentioning
confidence: 92%
“…Mobile technology helps disseminate information without a time limit [39]. According to the Human Rights Council of Australia [40], the efficient use of mobile technology contributes to a positive impact on rural farmers, and the surrounding community, and strengthens their positions in the market chain.…”
Section: Precision Farmingmentioning
confidence: 99%
“…According to the Human Rights Council of Australia [40], the efficient use of mobile technology contributes to a positive impact on rural farmers, and the surrounding community, and strengthens their positions in the market chain. The efficient use of mobile phones also encourages active participation to enhance the social status of farmers and economic development [39]. One of the reasons for failure in information technology intervention is an unsatisfactory design that does not meet the needs of technology users [41].…”
Section: Precision Farmingmentioning
confidence: 99%